Disaster Information System and Work Productivity of the Regional Disaster Management Agency (BPBD) of Palangka Raya City - Jaemi Wahyudi; Bayu Suratmoko; Ahyar Junaedi; Mohamad Rafii (Journal of Innovative and Creativity, 2025)
Purpose. This study aims to examine the implementation of disaster management information systems in improving work productivity at the Regional Disaster Management Agency (BPBD) of Palangka Raya City. The research focuses on how integrated organizational structures and the use of supporting technologies contribute to more effective disaster response and coordination. Materials and Methods. A qualitative approach was employed using data collection techniques including interviews, observations, and documentation. The study involved key informants from BPBD and utilized triangulation to ensure the validity of findings. Results. The findings indicate that the integrated structure of BPBD, supported by technologies such as the PERISAI application and the 112-emergency call centre service, has significantly improved data management and disaster response coordination. However, challenges remain in the form of limited human resources and low public awareness regarding the disaster information system. These limitations hinder the optimal utilization of the system and its potential benefits in disaster mitigation and response. Conclusions. Continuous staff training and intensive public outreach are needed to enhance understanding and participation in disaster mitigation efforts. The study highlights the importance of developing adaptive disaster information systems, strengthening human resource capacity, and increasing community education as key elements for effective disaster management at the regional government level